Support tools for paediatric inpatient prescribers: a review. Issue 2 (22nd August 2013) - Burridge, Alice Mary; Wilson, Keith; Terry, David
Abstract : Prescribing support for paediatrics is diverse and includes both standard texts and electronic tools. Evidence concerning who should be supported and by what method is limited. This review aims to collate the current information available on prescribing support in paediatrics. Many tools designed to support prescribers are technology based. For example, electronic prescribing and smart phone applications. There is a focus on prescriber education both at undergraduate and postgraduate level. In the UK, the majority of inpatient prescribing is done by junior medical staff. It is important to ensure they are competent on qualification and supported in this role. A UK national prescribing assessment is being trialled to test for competence on graduation and there are also tools available to test paediatric prescribing after qualification. No information is available on the tools and resources UK prescribers currently use to support their decision making. One US study reported a decrease in the availability of paediatric prescribing information in a popular reference text. There is limited evidence to show that decision-support tools improve patient outcomes, however, there is growing confirmation that electronic prescribing reduces medication errors. There have been reports of new error types, such as selection errors, occurring with the use of electronic prescribing. Another concern with computerised decision-support systems is deciding what alerts should be presented to the prescriber and when/how often in order to avoid alert fatigue. There is little published concerning paediatric alerts perhaps as a consequence of commercial systems often not including paediatric specific support.